Self-Directed Learning of Malay Undergraduate Students - Badli Esham Ahmad; Zuria Akmal Saad; Azwan Shah Aminuddin; Mohd Amli Abdullah (Studies in Self-Access Learning Journal)
This study investigated the self-directed learning readiness (SDLR) of 944 Malay undergraduate students in a Malaysian university, using Guglielmino’s Self-directed Learning Readiness Survey (1977), which is a 58-item Likert scale questionnaire that uses the Delphi technique to identify the level of SDLR of adult learners. Results indicate that the majority of the participants possess a moderate readiness level. The age-based analysis, though less relevant due to a predominantly young demographic, still indicates a need for facilitation in their learning journeys. These findings underscore the importance of tailored strategies and support mechanisms (i.e., guidance from instructors) to enhance educational outcomes.